Effects of different sodium–glucose cotransporter 2 inhibitors in heart failure with reduced or preserved ejection fraction: a network meta-analysis - Lan, Xiaohua; Zhu, Huijing; Cao, Yanjie; Hu, Yue; Fan, Xingman; Zhang, Kaijie; Wu, Mengdi (Frontiers in Cardiovascular Medicine, 2024)
Background This systematic review and meta-analysis aimed to explore the effects of different sodium–glucose cotransporter-2 inhibitors (SGLT2i) on prognosis and cardiac structural remodeling in patients with heart failure (HF). Methods Relevant studies published up to 20 March 2024 were retrieved from PubMed, EMBASE, Web of Science, and Cochrane Library CNKI, China Biomedical Literature Service, VIP, and WanFang databases. We included randomized controlled trials of different SGLT2i and pooled the prognosis data of patients with HF. We compared the efficacy of different SGLT2i in patients with HF and conducted a sub-analysis based on left ventricular ejection fraction (LVEF). Results We identified 77 randomized controlled trials involving 43,561 patients. The results showed that SGLT2i significantly enhanced outcomes in HF, including a composite of hospitalizations for HF and cardiovascular death, individual hospitalizations for HF, Kansas City Cardiomyopathy Questionnaire (KCCQ) scores, left atrial volume index (LAVi), and LVEF among all HF patients (P < 0.05) compared to a placebo. Sotagliflozin was superior to empagliflozin [RR = 0.88, CI (0.79–0.97)] and dapagliflozin [RR = 0.86, CI (0.77–0.96)] in reducing hospitalizations for HF and CV death. Dapagliflozin significantly reduced hospitalizations [RR = 0.51, CI (0.33–0.80)], CV death [RR = 0.73, CI (0.54–0.97)], and all-cause mortality [RR = 0.69, CI (0.48–0.99)] in patients with HF with reduced ejection fraction (HFrEF). SGLT2i also plays a significant role in improving cardiac remodeling and quality of life (LVMi, LVEDV, KCQQ) (P < 0.05). Among patients with HF with preserved ejection fraction (HFpEF), SGLT2i significantly improved cardiac function in HFpEF patients (P < 0.05). In addition, canagliflozin [RR = 0.09, CI (0.01–0.86)] demonstrated greater safety compared to sotagliflozin in a composite of urinary and reproductive infections of HFpEF patients. Conclusion Our systematic review showed that SGLT2i generally enhances the prognosis of patients with HF. Sotagliflozin demonstrated superiority over empagliflozin and dapagliflozin in a composite of hospitalization for HF and CV death in the overall HF patients. Canagliflozin exhibited greater safety compared to sotagliflozin in a composite of urinary and reproductive infections of HFpEF. Overall, the efficacy of SGLT2i was greater in HFrEF patients than in HFpEF patients.